Synthesis, Molecular Properties Estimations, and Dual Dopamine D2 and D3 Receptor Activities of Benzothiazole-Based Ligands - Schübler, Moritz; Sadek, Bassem; Kottke, Tim; Weizel, Lilia; Stark, Holger (Frontiers in Chemistry, 2017)
Neurleptic drugs, e.g. aripiprazole, targeting the dopamine D2s and D3 receptors (D2sR and D3R) in the central nervous system are widely used in the treatment of several psychotic and neurodegenerative diseases. Therefore, a new series of benz[d]thiazole-based ligands (1-18) was synthesized by applying the bioisosteric approach derived from the selective D3Rs ligand BP-897 and its structurally related benz[d]imidazole derivatives. Herein, introduction of the benz[d]thiazole moiety was well tolerated by D2sR and D3R binding sites leading to antagonist affinities in the low nanomolar concentration range at both receptor subtypes. Further exploration of different substitution patterns at the benz[d]thiazole heterocycle and the basic 4-phenylpiperazine resulted in the discovery of high dually acting D2sR and D3R ligands. Moreover, the methoxy substitution at 2-position of 4-phenylpiperazine resulted in significantly (22-fold) increased D2sR binding affinity as compared to the parent ligand BP-897, and improved physicochemical and drug-likeness properties of ligands 1-9. However, the latter structural modifications failed to improve the drug-able properties in ligands having un-substituted 4-phenylpiperazine analogues (10-18). Accordingly, compound 7 showed in addition to high dual affinity at the D2sR and D3R (Ki (hD2SR) = 2.8 ± 0.8 nM; Ki (hD3R) = 3.0 ± 1.6 nM), promising clogS, clogP, LE (hD2sR, hD3R), LipE (hD2sR, hD3R), and drug-likeness score values of -4.7, 4.2, (0.4, 0.4), (4.4, 4.3), and 0.7, respectively. Also, the deaminated analogue 8 (Ki (hD2SR) = 3.2 ± 0.4 nM; Ki (hD3R) = 8.5 ± 2.2 nM) revealed clogS, clogP, LE (hD2sR, hD3R), LipE (hD2sR, hD3R) and drug-likeness score values of -4.7, 4.2, (0.4, 0.4), (3.9, 3.5), and 0.4, respectively. The results observed for the newly developed benz[d]thiazole-based ligands 1-18 provide clues for the diversity in structure activity relationships (SARs) at the D2sR and D3R subtypes.